1978
DOI: 10.1159/000207712
|View full text |Cite
|
Sign up to set email alerts
|

Ethnical and Clinical Aspects of Chronic Lymphocytic Leukemia in Israel

Abstract: The ethnic distribution of 288 patients with chronic lymphocytic leukemia (CLL) from five medical centers in Israel during the decade 1960–1970 was investigated as well as other features of the disease. 80.5% of the patients were of East European descent, 14.5% originated from Asia and Africa and 5% were born in Israel. Based on the ethnic distribution of the elderly population of Israel during the above period, it is suggested that CLL occurs more frequently in European-born Jews than in Asian and African Jew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…A high incidence of CLL in Israel and a striking prevalence of CLL in Jews born in European-American countries (Ashkenazi Jews) in comparison to those originating from Asia and Africa (Sephardic Jews) has been reported previously. 12,19 This present study confirms the prevalence of CLL in Jews born in Europe and America. The majority of our CLL patients originated from Eastern Europeformer USSR, Poland, Romania.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A high incidence of CLL in Israel and a striking prevalence of CLL in Jews born in European-American countries (Ashkenazi Jews) in comparison to those originating from Asia and Africa (Sephardic Jews) has been reported previously. 12,19 This present study confirms the prevalence of CLL in Jews born in Europe and America. The majority of our CLL patients originated from Eastern Europeformer USSR, Poland, Romania.…”
Section: Discussionsupporting
confidence: 87%
“…11 In Israel, the survey of 288 cases of CLL in 1978 has shown that 80% of these individuals originated from the European countries (Ashkenazi Jews), whereas only 15% descended from Asia and Africa (Sephardic Jews). 12 The impact of ethnic origin of the patients on the pattern and prog-nosis of CLL is unknown. Our present study deals with a series of 302 B cell CLL and prolymphocytic leukemia (PLL) cases, originating from Eastern Europe, Asia and Africa, followed for up to 20 years in a Southern area of Israel.…”
Section: Introductionmentioning
confidence: 99%
“…The elderly occurrence of CLL was reinforced in this study, as the median age was 56 years with predominant peak in the age bracket, 56–60 years. That CLL with other B‐cell lymphoproliferative disorder is frequent in males has been reported (Bartal et al. , 1978; Hoffbrand et al.…”
Section: Discussionmentioning
confidence: 73%
“…This disparity has been attributed to a higher incidence of psychosomatism and a higher tendency to seek medical attention amongst females. A survey carried out in Israel over 2 decades ago showed a similar female dominance in patients of Africa descent unlike their European counterparts, which had a male dominance (Bartal et al. , 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Though we did not examine cellular immunity, concurrent hypogammaglobulinemia in our patient may have caused dysfunction of T cells and NK cells, and this, in turn, could have been associated with the development of the cancer. It has been demonstrated that CLL patients with an additional malignancy more often show low immunoglobulin levels than those patients without it, 20 and that T-cell abnormality is more prominent in CLL patients with hypogammaglobulinemia. 21 As the present patient showed an aggressive course of rectal cancer, the defective immunity may also have been associated with the rapid progression of the second malignancy.…”
Section: Discussionmentioning
confidence: 99%